BEYOND READING: ASSESSING STUDENTS' CRITICAL READING SKILLS IN ACADEMIC ARTICLE ANALYSIS - Yuniar; Khaerati Syam, Ummi; Sastrawati, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of critical reading skills of sixth-semester students of the English Language Education Study Program at Universitas Muhammadiyah Makassar in analyzing complex academic articles. Recognizing that critical reading is essential for academic success and future thesis writing, this research employed a descriptive quantitative design to systematically assess these competencies. The sample consisted of 32 sixth-semester students who participated fully in the study. Data were collected through a specially designed Critical Reading Test consisting of 25 multiple-choice questions. This instrument was formulated to accurately measure five core reading indicators across high-level cognitive processes: interpreting meaning, analyzing author bias, evaluating evidence, drawing valid conclusions, and synthesizing scientific information. The collected data were processed and analyzed using descriptive statistics with IBM SPSS Statistics version 25. The results revealed that the mean score of the students' critical reading ability was 94.75, with a median of 96.00, a mode of 96.00, and a standard deviation of 5.962. The minimum score obtained was 80, and the maximum score was 100. Based on the established classification criteria, 100% of the respondents (32 students) achieved the "Excellent" level. Notably, no students were classified into the Good, Average, Poor, or Very Poor categories. These findings indicate that the students possess outstanding higher-order thinking skills and an advanced capacity to effectively evaluate academic arguments, research methods, and scientific evidence. Ultimately, this high proficiency is closely linked to the successful curriculum integration of sequential reading courses and intensive research methodology training, which could serve as a valuable model for similar educational programs.